Perbedaan Jumlah Sel Neuron Cerebrum dan Cerebellum Mus musculus pada Kehamilan Remaja dan Dewasa - Tri Purwanti; Widjiati Widjiati; Muhammad Miftahussurur (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Teenage pregnancy contributes to emotional stress higher than adult women Pregnancy in adolescents will trigger negative thoughts and feelings of fear that become the root cause of stress reactions. The onset of stress will trigger the occurrence of Axis HPA activity and the release of corticotrophin releasing hormone (CRH) by the paraventricular nucleus of the hypothalamus, then stimulate the production of adrenencorticotropic hormone (ACTH) by the anterior pituitary gland. ACTH will stimulate glucocorticoids (cortisol) from the adrenal gland cortex to increase the production of CRH in the placenta and give an effect of increasing cortisol in the maternal, as well as the amount of cortisol in the fetus will also increase because it follows the blood placenta barrier. This affects the growth and development of the fetal brain, so that the process of proliferation and differentiation, migration, organization and synaptogenesis and myelination in brain cells. The growth of the brain decreases which affects the number of neuron cells. This study aims to analyze the differences in the number of neuron cells in the cerebrum and cerebellum Mus musculus newly born in adolescent and adult pregnancy. The division of the study group consisted of two groups, namely the adolescent and adult pregnancy groups each of 16 individuals. Taking the examination sample is by taking each of the 3 children from the parent with the heaviest, medium and lowest weights. Then the Mus musculus children were sacrificed by anesthesia and decapitation, then Hematoxilin-Eosin preparations were made from the child's brain. The next step is to examine Hematoxilin-Eosin to calculate the number of neuron cells in the cerebrum and cerebellum with the analysis of the Independent T test showing significant differences between the control and treatment groups with a value of p = 0,000 (p <0.05). Then the analysis of the number of brain neuron cells using the Mann Whitney test showed a difference that the control group was higher than the adolescent group.